The key dimensions of online service quality: a study of consumer perceptions. - Yapp, Emily,Hon Tshin (2014)
Service quality is one of the major aspects of success of any business, including online retailing. This study attempts to identify the key dimensions of online service quality as perceived by the online air ticket buyers. The six key dimensions identified are promptness/ reliability, personalization, website content, flexibility, trustworthiness and ease of navigation. The results further reveal that all these six dimensions have a positive influence on online buyers’ evaluation of overall service quality. Out of these six key dimensions, personalization followed by trustworthiness are identified as the most influential service quality dimensions in achieving a higher level of overall service quality as perceived by online buyers.